2000
DOI: 10.1161/01.str.31.12.2971
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 in Subarachnoid Hemorrhage

Abstract: Background and Purpose-The most potent vasoconstrictor known, endothelin-1, is currently considered to mediate cerebral vasospasm in subarachnoid hemorrhage (SAH), which can cause delayed cerebral ischemia. In our study, we performed clinical and in vitro experiments to investigate the origin and the mechanisms of the secretion of endothelin-1 in SAH. Methods-Endothelin-1 and markers of inflammatory host response (interleukin [IL]-1␤, IL-6, and tumor necrosis factor-␣) were comparatively quantified in the cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…ET-1 has been detected in CSF from patients with SAH and can be produced by monocytes isolated from CSF of SAH patients [13, 14]. ET-1 has been implicated in the development of vasospasm after SAH [15] and will be discussed in detail later in this review.…”
Section: Evidence For Acute Inflammation After Subarachnoid Hemorrmentioning
confidence: 99%
See 1 more Smart Citation
“…ET-1 has been detected in CSF from patients with SAH and can be produced by monocytes isolated from CSF of SAH patients [13, 14]. ET-1 has been implicated in the development of vasospasm after SAH [15] and will be discussed in detail later in this review.…”
Section: Evidence For Acute Inflammation After Subarachnoid Hemorrmentioning
confidence: 99%
“…ET-1 has been implicated in the development of vasospasm after SAH [15] and will be discussed in detail later in this review. As with many other proinflammatory molecules, the expression of ET-1 is highly variable: in a study by Fassbender and colleagues, ET-1 was not found in CSF of control subjects, and only 46% of patients with SAH had detectable levels of ET-1 [13]. Though the averaged results of both groups revealed a significant increase in ET-1 after SAH, this demonstrates that not all patients with SAH experience the same inflammatory response.…”
Section: Evidence For Acute Inflammation After Subarachnoid Hemorrmentioning
confidence: 99%
“…ET-1 is a potent vasoconstrictor released by astrocytes and leukocytes in response to inflammation and early ischemia after SAH [68, 69]. ET-1 is implicated in early brain injury and in the pathogenesis of delayed vasospasm and delayed ischemic deficits after SAH [7072].…”
Section: Early Brain Injury By Sahmentioning
confidence: 99%
“…Accumulating pro and contra evidence related to endothelin-1 [14,15,16,17,18], in a phase II randomized clinical trial (RCT) of clazosentan, a selective endothelin A receptor antagonist, it was found that clazosentan significantly reduced the incidence of ‘moderate to severe (<67% of control) vasospasm on the angiogram’, from 88% in placebo-treated individuals to 40% in the treated group (n = 32) [19]. However, the results of the latest phase III RCT (n = 1,157) did not demonstrate a beneficial effect of the drug in patients with SAH as regards functional outcome, vasospasm-related morbidity or mortality.…”
Section: Introductionmentioning
confidence: 99%